Malaysia Royal Customs and the e-Eksais System: Review and Prospect (Journal of Governance and Development (JGD), 2007)
The e-Eksais system is a pre-Internet solution for faster processes involving the excise duties and sales tax payment between automobile manufacturers and the Malaysia Royal Custom (MRC). Being the second most important revenue raiser agency to the government, MRC had developed the e-Eksais system to provide efficient process in collecting billions of excise duties and sales taxes from local automobile manufacturers. The system utilises the electronic data interchange (EDI) to expedite the vehicle release process of and payment of excise duties from manually to electronics forms. The system claims to benefit the manufacturers’ clients and MRC in staff and cost efficiency. The e-Eksais service is getting matured where the take-up and usage of e-Eksais is almost extended to most local automobile manufacturers and dealers. However, the state of the art of the MRC’s information and technologies clients systems needs to incorporate a Web-based system to allow for wider usage and a low cost means of interacting with MRC.